ISOLASI DAN KARAKTERISASI BACILLUS LIPOLITIK DARI TANAH KEBUN RAYA LIWA - Vidia Royanti; Kusuma Handayani; Chistina Nugroho Ekowati; Sumardi Sumardi (Gunung Djati Conference Series, 2023)
Bacillus is a bacterium that has the ability to survive in unfavorable environmental conditions, one of which is in nutrient-poor soils such as the Liwa Botanical Gardens. Bacillus isolates have been obtained from the soil of the Liwa Botanical Gardens which have lipolytic abilities. This study aimed to determine the activity of lipolytic bacteria isolates from Bacillus from Liwa Botanical Gardens. In this study, Bacillus was isolated from the soil of the Liwa Botanical Gardens using a graded dilution method, using Nutrient Agar media. The Bacillus isolates obtained were then purified in Nutrient agar media. Bacillus isolates were inoculated in lipase test media with a composition of 0.01% methyl red, 10 g peptone, and Nutrient Agar, 5% sterile olive oil, 2.5% Tween-80, 5 g NaCl, 0.1 g CaCl2.2H2O. The results of this study obtained 5 isolates of Bacillus which had fairly good growth, namely isolates BP 13, BP 14, BP16, TMA 13, TSR 5. With the results obtained the largest lipolytic activity was isolate BP 16 with an average index value of 6.34 cm while the lowest lipolytic activity was TMA13 isolate with an average index value of 2,345 cm.